IPTEKS PENGENDALIAN INTERN ATAS PENGELOLAAN BARANG MILIK DAERAH DI DINAS KOMUNIKASI INFORMATIKA PERSANDIAN DAN STATISTIK DAERAH PROVINSI SULAWESI UTARA - Pagora, Inggi; Pulu, Elisya; Gerungai, Natalia Y. T. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The study aims to determine the internal control over the management of Regional Property in the Office of Communication, Information, Regional Statistics and Statistics of North Sulawesi Province. Internal control of regional property, which is one of the important parts in realizing good financial statements. Because internal control includes management and registration of Regional Property. Internal Control of Regional Property at the Office of Communication, Information, Regional coding and Statistics of North Sulawesi Province has not gone well because there are risks that hinder the Internal Control but the Office of Communication, Information, Regional coding and Statistics of North Sulawesi Province. Although it can handle it, such as conducting control activities, where these activities must be carried out by the leadership of organizational units and functional personnel both in their respective environments and between organizational units within the Regional Government in accordance with their respective objectives, in order to provide information and communication services that adequate to the community, but it has not gone well because the organizational unit leaders and functional staff have not carried out their duties and responsibilities in accordance with existing regulations.Keywords: Internal Control of Regional Property